Advanced Maternal Age: Adverse Outcomes of Pregnancy, A Meta-Analysis - Pinheiro, Rosa Lomelino (2019)
The risks of pregnancy in women of advanced maternal age are not consensual amongst studies. The aim of this metaanalysis  was to determine whether women of advanced maternal age (≥ 35 years old) had worse obstetrical and perinatal outcomes than non- advanced maternal age women (20 - 34 years old) in singleton, naturally-conceived pregnancies.Material and Methods: We searched PubMed/ MEDLINE, IndexRMP and the Cochrane Database of Systematic Reviews. Ten studies were included according to the following criteria: population of > 1000 nulliparous and/or multiparous women with singleton gestations who did not undergo any type of infertility treatment. Using Review Manager v. 5.3, two meta-analysis were performed: one comparing the outcomes of 20 - 34-year-old vs 35 - 40-year-old women, and another comparing the outcomes of 35 - 40-year-old women vs > 40-year-old women. Results: Women aged 35 - 40 years old were more likely to have > 12 years of education than 20 - 34 years old and > 40 years old women. Advanced maternal age women (35 - 40 and > 40 years old) were more likely to be overweight and having gestational diabetes and gestational hypertension. They were also more likely to undergo induced labour and elective caesarean deliveries. Furthermore, they had worse perinatal outcomes such as preterm delivery, low birthweight babies, higher rates of Neonatal Intensive Care Unit admission and worse Apgar scores. Advanced maternal age women had higher rates of perinatal mortality and stillbirth. Discussion: Most authors present similar results to our study. Although the majority of adverse outcomes can be explained through the physio-pathological changes regarding the female reproductive apparatus that come with aging and its inherent comorbidities, according to the existing literature advanced maternal age can be an independent risk factor per se. In older pregnant women without comorbidities such as gestational hypertension or diabetes there are still worse obstetric and perinatal outcomes, which indicate that advanced maternal age is an independent strong risk factor alone. Conclusion: Advanced maternal age women are at a higher risk of adverse obstetrical and perinatal outcomes. In both comparisons, worse outcomes were more prevalent in the older group, suggesting that poorer outcomes are more prevalent with increasing age.